2016
DOI: 10.1007/978-3-319-49409-8_32
|View full text |Cite
|
Sign up to set email alerts
|

ChaLearn LAP 2016: First Round Challenge on First Impressions - Dataset and Results

Abstract: This paper summarizes the ChaLearn Looking at People 2016 First Impressions challenge data and results obtained by the teams in the first round of the competition. The goal of the competition was to automatically evaluate five "apparent" personality traits (the so-called "Big Five") from videos of subjects speaking in front of a camera, by using human judgment. In this edition of the ChaLearn challenge, a novel data set consisting of 10,000 shorts clips from YouTube videos has been made publicly available. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
154
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 140 publications
(164 citation statements)
references
References 42 publications
0
154
0
Order By: Relevance
“…Inherited from them, most of latest face recognition methods consider the task as a multi-class classification problem and train deep face features on large public datasets such as LFW [17], VGG-Face [10] or FaceNet [18]. While it has been shown that the trained representations are, to some extent, transferable between face recognition and affective computing [3,19], a direct application of shared CNN representations trained for both emotion and personality without large-scale datasets encompassing both emotion and personality annotations is rarely studied. Inspired by the recent advances in face recognition achieved by lightstructured networks [20], we introduce PersEmoN with a SphereFace [20] based network backbone to show thatsuch a strategy is advantageous.…”
Section: Deep Learning For Face Recognitionmentioning
confidence: 99%
See 3 more Smart Citations
“…Inherited from them, most of latest face recognition methods consider the task as a multi-class classification problem and train deep face features on large public datasets such as LFW [17], VGG-Face [10] or FaceNet [18]. While it has been shown that the trained representations are, to some extent, transferable between face recognition and affective computing [3,19], a direct application of shared CNN representations trained for both emotion and personality without large-scale datasets encompassing both emotion and personality annotations is rarely studied. Inspired by the recent advances in face recognition achieved by lightstructured networks [20], we introduce PersEmoN with a SphereFace [20] based network backbone to show thatsuch a strategy is advantageous.…”
Section: Deep Learning For Face Recognitionmentioning
confidence: 99%
“…2. For personality, we use the ChaLearn personality dataset [3], which consists of 10k short video clips with 41.6 hours (4.5M frames) in total. In this dataset, people face and speak to the camera.…”
Section: Dataset and Evaluation Protocolmentioning
confidence: 99%
See 2 more Smart Citations
“…In this work, we investigate AGC analysis from an early prediction perspective. This can also be viewed as a first impression of a group's cohesion, similar to the early personality assessment [12] problem in affective computing. The main contributions of this paper are as follows:…”
Section: Introductionmentioning
confidence: 99%